Sistem Informasi Geografis Sebaran Titik Panas Di Provinsi Jambi - Wirmaini, Wirmaini; Kurniabudi, Kurniabudi (LPPM Universitas Dinamika Bangsa, 2023)
Hotspots are an indicator of forest and land fire disasters that occur every year in Indonesia, especially Sumatra and Kalimantan, which have peatlands. Jambi Province, one of the provinces in Sumatra that has peatlands, experienced land and forest fires. The problem faced today is that there is no information system that can display information data on the distribution of hot spots in Jambi Province in real time. The purpose of this research is to analyze problems and design a geographic information system for the distribution of web-based hot spots. The research method uses a prototype model and a unified model language system model using usecase diagrams, activity diagrams, and class diagrams. The results of this study are in the form of a prototype design for geographical information on the distribution of web-based hot spots that can be implemented later as a solution to existing problems